Light Stimulation of Neurons on Organic Photocapacitors Induces Action Potentials with Millisecond Precision (Adv. Mater. Technol. 9/2022). Issue 9 (16th September 2022) - Schmidt, Tony; Jakešová, Marie; Đerek, Vedran; Kornmueller, Karin; Tiapko, Oleksandra; Bischof, Helmut; Burgstaller, Sandra; Waldherr, Linda; Nowakowska, Marta; Baumgartner, Christian; Üçal, Muammer; Leitinger, Gerd; et al.
Abstract : Photocapacitors In article number 2101159, Eric Daniel Głowacki, Theresa Rienmüller, Rainer Schindl, and co‐workers present thin and flexible organic electrolytic photocapacitors (OEPCs) suitable for neuro‐stimulation. Like photovoltaic cells, these organic semiconductors have a photosensitive pn‐layer. OEPCs generate in an electrolytic environment an electric field when illuminated with visible red light, which is capable of inducing action potential firing in excitable cells.